3rd ICTs and Society Meeting; Paper Session - Theorizing the Internet; Paper 1: Toward Trust as Result. A Transdis- ciplinary Research Agenda for the 'Future Internet'. (2010) - Paoli, Stefano De; Gangadharan, G. R.; Kerr, Aphra; D'Andrea, Vincenzo; Serrano, Martin; Botvich, Dmitri; McGibney, Jimmy
No abstract available